Håkan Rydving, Tracing Sami Traditions. In Search of the Indigenous Religion among the Western Sami during the 17th and 18th Centuries - Sundström, Olle (Journal of Northern Studies, 2012)
Review of: Håkan Rydving, Tracing Sami Traditions. In Search of the Indigenous Religion among the Western Sami during the 17th and 18th Centuries (Instituttet for sammenlignende kulturforskning, Serie B, Skrifter 135), Oslo: The Institute for Comparative Research in Human Culture, Novus forlag 2010, ISBN 9788270995431, 168 pp.